2015
DOI: 10.1093/schbul/sbv030
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Excitatory Input to the Nucleus Accumbens in Schizophrenia: A Postmortem Ultrastructural Study

Abstract: The cause of schizophrenia (SZ) is unknown and no single region of the brain can be pinpointed as an area of primary pathology. Rather, SZ results from dysfunction of multiple neurotransmitter systems and miswiring between brain regions. It is necessary to elucidate how communication between regions is disrupted to advance our understanding of SZ pathology. The nucleus accumbens (NAcc) is a prime region of interest, where inputs from numerous brain areas altered in SZ are integrated. Aberrant signaling in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 106 publications
1
38
0
1
Order By: Relevance
“…Sources of GABAergic afferents to the SN include neurons that comprise the striatal direct pathway and neurons in the globus pallidus externus (Haber and Fudge, 1997). Schizophrenia subjects exhibit increased striatal glutamate tone (de la Fuente-Sandoval et al, 2011 and number of glutamatergic synapses in comparison with NCs McCollum et al, 2015; Figure 4a). It is possible that the extra stimulation provided by the glutamatergic input onto the GABAergic striatal neurons produces an increase in GAD and GABA in the SN.…”
Section: Dopamine and Gaba Dysregulation In Schizophreniamentioning
confidence: 99%
“…Sources of GABAergic afferents to the SN include neurons that comprise the striatal direct pathway and neurons in the globus pallidus externus (Haber and Fudge, 1997). Schizophrenia subjects exhibit increased striatal glutamate tone (de la Fuente-Sandoval et al, 2011 and number of glutamatergic synapses in comparison with NCs McCollum et al, 2015; Figure 4a). It is possible that the extra stimulation provided by the glutamatergic input onto the GABAergic striatal neurons produces an increase in GAD and GABA in the SN.…”
Section: Dopamine and Gaba Dysregulation In Schizophreniamentioning
confidence: 99%
“…Recent postmortem studies have suggested glutamatergic input to this region is increased. 6,7 The NMDA receptor and group 1 mGluRs are primary glutamatergic receptors expressed on striatal neurons and are important for neuronal signalling and neurotransmitter tone. In the present study we show that protein expression of the NMDA receptor subunits (NR1, NR2A and NR2B), group 1 mGluRs (total, dimeric and monomeric forms) and group 1 mGluR regulators (Norbin and Homer1b/c) are not altered in the NAcc in individuals who had schizophrenia, which is in contrast to previous reports on cortical and hippocampal brain regions.…”
Section: Discussionmentioning
confidence: 99%
“…McCollum and colleagues 7 reported an increase in asymmetric glutamatergic synapse number in the NAcc in a separate schizophrenia cohort, a finding that was specific to the core and not the shell of the NAcc, accompanied by a reduction in the area of the postsynaptic density (PSD) in asymmetric synapses. Furthermore, alterations of PSD membrane-associated guanylate kinases (MAGUK), SAP-102 and SAPAP1 expression have also been observed in the NAcc of schizophrenia cohorts, 40,41 suggesting alterations of scaffolding and signalling proteins within postsynaptic sites of the NAcc in schizophrenia pathology.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations